Livelihood Option through Trout Seed Production in Jammu and Kashmir: An Economic Analysis - Gawa, Stanzin; Kumar, Nalini Ranjan; Mahida, Navghan; Hatte, Vinay Maruti (Fishery Technology, 2017)
The present study was conducted during the period 2014-15 to understand the economics of trout seed production in the state of Jammu and Kashmir. It was observed that the trout seed production is a capital intensive business, with high cost involved in the establishment of fixed inventories. The study showed that 79.65% of seed produced in the state is used for culture purpose while 20.35% is utilized to stock the springs and streams for sports fisheries. The major capital investment was incurred in hatchery construction (around 90 lakh), which accounted 72.25% of the total capital investment. Cost and return analysis revealed fixed cost about ` 55.24 lakh and variable cost about ` 2.42 lakh which accounted about 95.63 and 4.37% respectively. The major constraints encountered in trout seed production was lack of skill labour and low demand for trout seed. Due to low demand for trout seed the trout hatcheries were running at a sub-optimal level but the demand for trout seed is expected to rise with increasing number of private trout farmers. With proper skill enhancement the trout hatchery business can transform into a viable livelihood option for entrepreneurs.